Cultivating green workforce: The roles of green shared vision and green organizational identity - Ma, Xuejun; Bashir, Hasnain; Ayub, Arslan (Frontiers in Psychology, 2023)
With an emphasis on the social identity theory (SIT) and social exchange theory (SET), the present study aims to investigate the association between green talent management (GTM) and employee retention (ER), mediated by green organizational identity (GOI) and moderated by green shared vision (GSV). We collected time-lagged (i.e., three-wave) data from frontline managers in the tourism service firms in Pakistan. Data are analysed using SmartPLS SEM (V 3.3) to evaluate the measurement model and the structural model. The findings reveal that GOI significantly mediates the relationship between GTM and ER. In addition, the moderator effect of GSV significantly underpins the direct association between GTM and GOI and the indirect association between GTM and ER, mediated by GOI. We examined a hitherto unexplored moderated mediation model to explain when and how tourism service firms can promote ER through inculcating GTM strategies. The findings indicate that service firms in the tourism industry require an imperative to develop and retain green talent to exploit pro-environmental strategies.